O´DONNELL GUILLERMO, OSVALDO IAZETTA Y JORGE VARGAS CULLELL (EDS.). 2003. DEMOCRACIA, DESARROLLO HUMANO Y CIUDADANÍA. SANTA FE: HOMO SAPIENS EDICIONES, 357 PP. - Valdivieso, Patricio (Revista de Ciencia Política, 2020)
No presenta resumen